Latin American and Caribbean Petroleum Engineering Conference 2009
DOI: 10.2118/122786-ms
|View full text |Cite
|
Sign up to set email alerts
|

Design of a High-Pressure Research Flow Loop for the Experimental Investigation of Liquid Loading in Gas Wells

Abstract: Liquid loading in producing gas wells is the inability of the produced gas to remove produced liquids from the wellbore. A review of existing flow loops worldwide revealed that specialized areas of research such as liquid loading in gas wells are still lacking dedicated test facilities. This project presents the design of a new dedicated facility to be located at the TowerLab at the Richardson building with adequate operating conditions to reproduce the flow regimes encountered prior to and after the onset of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Planning the right deliquification technique plays a very important role in reducing the risk of implementation failure and returns on investment in wells produced. [1] Turner et al (1969) observed the characteristics of liquid loading in a number of wells in the US onshore field using 106 data points. They found that a freefalling particle in a fluid medium will reach a terminal velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Planning the right deliquification technique plays a very important role in reducing the risk of implementation failure and returns on investment in wells produced. [1] Turner et al (1969) observed the characteristics of liquid loading in a number of wells in the US onshore field using 106 data points. They found that a freefalling particle in a fluid medium will reach a terminal velocity.…”
Section: Introductionmentioning
confidence: 99%